Menelisik Metodologi Tafsir Kontemporer: Studi atas Safīnah Kallā Saya’lamūn fī Tafsīri Shaikhinā Maimūn karya Ismail Al-Ascholīy - Saichul Anam (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2024)
This study focuses on the methodology employed by Ismail Al-Ascholiy in his interpretation of Safīnah Kalla Sayaʾlamūn fī Tafsīr Shaikhinā Maimūn. As a tafsir text that emerges from KH Maimun Zubair’s interpretive transcripts, this work offers a new nuance and appears somewhat unfamiliar within the spectrum of Indonesian tafsir. Hence, it serves as an appealing locus for research on Indonesian tafsir, given the absence of a comprehensive methodological study on this particular tafsir text. To examine the methodology of Safīnah Kalla Sayaʾlamūn fī Tafsīr Shaikhinā Maimūn, this research draws upon Islah Gusmian’s theoretical framework of tafsir book methodology and employs a qualitative approach in the form of content analysis. The findings indicate that Safīnah is presented thematically. In clarifying its verses, the tafsir tends to explain them globally using a popular writing style, which does not fulfill formal academic standards. This is because it was neither intended for academic purposes nor written under the auspices of any institutional affiliation. Judging by its method, this tafsir adopts a contextual approach by incorporating historical elements and reason, thereby producing a distinctly social nuance in its interpretation.